Constructing Groupings by Use of STATISTICA Software Package - V. S. Fetisov (Статистика України, 2018)
STATISTICA software package for statistical analysis incorporates a wide range of advanced statistical methods. Quite often they are preceded by aggregating statistical survey data, which main component is their grouping. Although this phase of statistical data processing is relatively simple, the manual process of aggregation can be time-consuming given the need to process large data arrays, not mentioning a high probability of errors. Therefore, the all-purpose STATISTICA software package is a logical and reasonable tool for grouping of data.